2011
DOI: 10.1007/s11165-011-9260-3
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Research-Informed Socio-scientific Activism: Re/Visions for a Sustainable Future

Abstract: In many educational contexts throughout the world, increasing focus has been placed on socio-scientific issues; that is, disagreements about potential personal, social and/or environmental problems associated with fields of science and technology. Some suggest (as do we) that many of these potential problems, such as those associated with climate change, are so serious that education needs to be oriented towards encouraging and enabling students to become citizen activists, ready and willing to take personal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 33 publications
0
34
0
8
Order By: Relevance
“…Indeed, researchers (Crowley et al, 2015) have found that participation in outdoor learning opportunities can be motivating for many students and help to reverse dissatisfaction with science back in the classroom. Bencze, Sperling and Carter (2012) suggest that practical work in real life contexts, and with an underlying social justice agenda, can also provide the answer to the oft-asked student question of "why are we learning this stuff?" Moreover, we note that the particular skills related to natural history activities specifically -that of observation, looking for patterns, justifying explanations (Eberbach & Crowley, 2005) and also systems thinking (Wals, 2014) -are essentially the building blocks of all scientific thinking.…”
Section: In the Classroommentioning
confidence: 99%
“…Indeed, researchers (Crowley et al, 2015) have found that participation in outdoor learning opportunities can be motivating for many students and help to reverse dissatisfaction with science back in the classroom. Bencze, Sperling and Carter (2012) suggest that practical work in real life contexts, and with an underlying social justice agenda, can also provide the answer to the oft-asked student question of "why are we learning this stuff?" Moreover, we note that the particular skills related to natural history activities specifically -that of observation, looking for patterns, justifying explanations (Eberbach & Crowley, 2005) and also systems thinking (Wals, 2014) -are essentially the building blocks of all scientific thinking.…”
Section: In the Classroommentioning
confidence: 99%
“…Essa validação da meritocracia é a discussão específica que o 3% traz (por Luísa Dalgalarrondo, 23 Este ativismo não deixa de poder ser visto como próximo àquele que autores como Derek Hodson 26 e Larry Bencze 27 defendem, um ativismo que se desenvolve em contexto escolar e que representa uma ação sociopolítica coletiva, levada a cabo pelos alunos, cujo propósito seja contribuir para a resolução de problemas sociocientíficos e socioambientais. 28 "Cinema e Debate" com Elysium: um breve relato de experiência Durante a greve que envolveu professores e estudantes da Rede Estadual de Educação do Rio de Janeiro, marcada por diversos movimentos, inclusive ocupações por estudantes, apoiados ou não por professores, em meados de maio de 2016, foi proposta uma roda de conversa "Cinema e Debate" a partir de cenas dos filmes Elysium, entre estudantes do Ensino Médio, pais, professores, entre outros cidadãos, no Colégio Estadual Barão de Aiuruoca, localizado no município de Barra Mansa/RJ.…”
Section: Elysium E Outras Ficçõesunclassified
“…A l'extrémité chaude du continuum, l'objectif va au-delà de l'apprentissage scientifique et vise l'engagement militant des apprenants dans des actions. L'activisme peut viser la justice sociale et environnementale et tente de favoriser un désir de changement ainsi que le sens des responsabilités chez les individus (Bencze et al, 2012). Ces auteurs suggèrent que les élèves/étudiants travaillent sur des projets de recherche ouverts et conduits par eux-mêmes.…”
Section: Emergence De La Didactique Des Questions Socialement Vives (unclassified